A survey of pediatric oncology nurses' oral health knowledge, attitudes, practices, and perceived barriers in a Singapore Tertiary Children's Hospital - Ruixiang Yee; Pui Ling Chay; Melissa Mei-Yi Khor; Yvonne Siew Ling Lim; Nicole Kim Luan Lee; Wee Fang Kam; Seyad Ehsan Saffari; Mei Yoke Chan (Nature Publishing Group, 2023)
Abstract Aim To explore oral health-related knowledge, abilities, attitudes, practices, and barriers of pediatric oncology nurses at an Asian children's hospital. Methods A cross-sectional study was conducted via a self-administered anonymized questionnaire. Data was analyzed to summarize knowledge, confidence, and practice behaviors. Results All sixty-three pediatric oncology nurses responded. Fifteen participants had >80% of the knowledge questions correct. Majority (97.3%) agreed on their roles in helping patients maintain their oral health. However, 75.8% of participants felt need for training in giving oral health advice. Notably, 74.6% checked patients' mouths at least once daily but only 57.1% felt adequately trained. Though a high proportion (>90%) of nurses felt confident to assist with oral care, only 65% would assist patients to do so; "Uncooperative patient" was the major barrier reported. Discussion Nurses have high general awareness of importance of oral health, but had incomplete knowledge. Compared to previous studies, most (90.5%) did not find performing oral care unpleasant but other barriers might have hindered actual oral care practice. Conclusion Nurses were motivated to assist in oral care of children with cancer but sometimes felt ill-equipped. Updated national and institution guidelines, didactic and hands-on training, and implementation of practical support could be considered.